A Combination of Flavonoids Suppresses Cell Proliferation and the E6 Oncogenic Pathway in Human Papillomavirus-Transformed Cells - Federico De Marco; Fabio Altieri; Stefano Giuliani; Italia Falcone; Susanna Falcucci; Mariassunta Tedesco; Roberto Becelli (Pathogens)
Despite the availability of excellent HPV-specific vaccines, HPV-related conditions and, notably, their related neoplastic diseases are expected to impact human health for many years to come. Polyphenols and flavonoids are a large class of natural products, credited with a wide range of pharmacological properties including antineoplastic activity. However, the currently available data depict a rather heterogeneous and sometimes contradictory landscape, and no univocal conclusions can be drawn. To shed light on such a controversial issue, a restricted list of promising polyphenols were evaluated for their antineoplastic activity on HPV-transformed cells. Among them, Kaempferol, Galangin, and Luteolin proved to have distinct anti-clonal activity with ID50 values, respectively, of 1.25, 6.25, and 3.0 microMolar, and three other compounds, namely, Chrysin, Quercetin, and Apigenin, showed fair although less intense activity with ID values, respectively, of 25.0, 40, and 25 microMolar. Interestingly, a distinct anti-proliferative effect could also be suggested for Kaempferol, Luteolin, and Apigenine. Cooperative anti-clonal effects could be suggested for binary and ternary compositions made of Kaepferol, Galangin, and Luteolin once combined at concentrations ranging from 2 to 8 microMolar. At these concentrations, the single components and the triple combination induced distinct cell cycle modulation associated with marked restoration of the p53 and p21Cip1/Waf1 levels, consistent with the disruption of the E6/E6AP interaction whose continuous activity is necessary for both the induction and maintenance of the viral-induced neoplastic phenotype.